Problems of the legal status of private farms - Milyausha T. Lukyanova, Sofya E. Khasanova, Evgeny V. Balashov, Ravil H. Gizzatullin Igor A. Vladimirov, Radmir A. Iksanov, (Opción, 2020)
The aim of the study is to determine the features of the legal status of personal subsidiary farms, the possibilities of participation of personal subsidiary farms in cooperative activities. Legal and statistical methods were used to achieve this goal. As a result, the necessity of relationship building between the owners of private farms with the state authorities on the participation of private farms in the state target programs is revealed. In conclusion, when adopting new acts regulating the activities of private farms, the legislator must take into account the essential differences between commodity and consumer farms of citizens.